Committee on Tax and Financial Entity Theory. (The Accounting Review, 1973)
The article presents a report of the Committee on Tax and Financial Entity Theory of the American Accounting Association, which aimed to compare and contrast the entity concept, associated with financial accounting to that associated with Federal income taxation. An examination of the existing literature suggests that professional and scholarly writings in both financial accounting and income taxation contain numerous viewpoints or equity theories, which advocate a theory as the proper one for all purposes. The 1964 American Accounting Association Committee's definition of the entity concept was used as a focal point. For financial accounting, the liquidation of a corporate unit would result in the recognition of gain or loss to the corporate unit before transferring the assets to the shareholders. The Code provisions covering collapsible corporations were designed to prevent the conversion of ordinary income to capital gain.